Rural-urban health disparities among older adults in South Africa - Karl Peltzer; Nancy Phaswana-Mafuya; Supa Pengpid (AOSIS, 2019)
Background: There are limited studies assessing rural-urban disparities among older adults in Africa including South Africa. Aim: This study explores rural-urban health disparities among older adults in a population-based survey in South Africa. Setting: Data for this study emanated from the 2008 study on 'Global Ageing and Adult Health (SAGE) wave 1' (N = 3280) aged 50 years or older in South Africa. Methods: Associations between exposure variables and outcome variables (health status variables and chronic conditions) were examined through bivariate analyses and multivariable logistic regression. Results: Rural dwellers were more likely to be older, black African and had lower education and wealth than urban dwellers. Rural and urban dwellers reported a similar prevalence of self-rated health status, quality of life, severe functional disability, arthritis, asthma, lung disease, hypertension, obesity, underweight, stroke and/or angina, low vision, depression, anxiety and nocturnal sleep problems. Adjusting for socio-demographic and health risk behaviour variables, urban dwellers had a higher prevalence of diabetes (OR: 2.36, 95% CI: 1.37, 4.04), edentulism (OR: 2.79, 95% CI: 1.27, 6.09) and cognitive functioning (OR: 1.91, 95% CI: 1.27, 2.85) than rural dwellers. Conclusion: There are some rural-urban health disparities in South Africa, that is, urban dwellers had a higher prevalence of diabetes, edentulism and cognitive functioning than rural ones. Understanding these rural-urban health variations may help in developing better strategies to improve health across geolocality in South Africa.